1990
DOI: 10.1136/bjsm.24.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Strength training for wheelchair users.

Abstract: Sedentary adult males with spinal lesions, all habitual wheelchair users, were allocated to exercise (n = 11) and control (n = 4) groups. A Cybex II dynamometer was used to assess peak power, average power, total work and muscular endurance for elbow flexion/extension, shoulder flexion/extension and shoulder abduction/adduction at five angular velocities, on recruitment and after eight and 16 weeks of forearm ergometer training (three days/week). Small sub-groups of the exercised subjects were assigned to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…After reading the 40 papers (LV: PhD student and ET: MSc in Human Movement Science; both experienced in physical therapy research methods), 15 training studies were excluded for the following reasons: other outcome measures, [15][16][17][18][19][20][21][22][23] mixed population, 24,25 the population was not described properly, 26 training of both arms and legs 27 or -as was the case in two papers -the results were already published in other included papers. 28,29 The 25 included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the 40 papers (LV: PhD student and ET: MSc in Human Movement Science; both experienced in physical therapy research methods), 15 training studies were excluded for the following reasons: other outcome measures, [15][16][17][18][19][20][21][22][23] mixed population, 24,25 the population was not described properly, 26 training of both arms and legs 27 or -as was the case in two papers -the results were already published in other included papers. 28,29 The 25 included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…All studies claim significant improvements in muscle strength, but again, no control groups were present in any of the studies involved. Other upper body training studies in spinal cord injury, 16,18,19 all excluded from this review because they lacked data on VO 2peak and PO peak , also reported improvement in muscle strength.…”
Section: Other Outcome Measuresmentioning
confidence: 99%
“…Unfortunately, the vast majority of longitudinal studies have been relatively short in duration (524 weeks), restricted to either persons with paraplegia or persons with tetraplegia, and have been rather narrow in their focus on outcome measures. For example, studies have examined the e ects of exercise training on either cardiorespiratory function 7,9 or muscle strength, 12,13 but relatively few have included both strength and cardiovascular endurance measures in their outcomes, and fewer still have included measures of quality of life (QOL). One study, more than two decades ago, attempted to include multiple outcome measures, 14 and they reported signi®cant improvements in exercise capacity (31%), maximum oxygen uptake (12%), and strength (19%) after 7 weeks of thrice-weekly training in persons with incomplete paraplegia.…”
Section: Introductionmentioning
confidence: 99%
“…In those studies, training consisted of moderate intensity exercises with arm, kayak and wheelchair ergometers [15][16][17] . Especially, individuals with SCI have physiological disavantages limiting exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Olenik et al 14 reported that strengthening and stretching exercises may be beneficial to correct imbalances of the muscles in the upper extremity. Some studies have examined the effect of circuit training training and rehabilitation in wheelchair users 15,16 , but there is a lack of studies on strength training in WCB athletes 17 . As far as we know, no studies have reported the effects of short-duration explosive strength training in WCB athletes.…”
Section: Introductionmentioning
confidence: 99%